Zdrowie psychiczne dzieci i rodziców w sytuacji ich izolacji w wyniku rozpadu rodziny - Iwona Rawicka (Studia Paradyskie)
Family breakdown is a difficult experience to all its members. Both for children and adults separation may bring a lot of consequences revealing problems with maintaining mental health. The aim of this article is to present situations, in which a family breakdown causes isolating the child by one of the parents from the other one who is not living with the rest of the family. The analysis of the results of the research indicates the risk of cognitive and emotional consequences not only in children isolated from their parents but also in adults, whose contact with their own children is restricted by their ex-spouse. It turns out that both adults and children may reveal reactions and behaviour indicating mental disorders.